Grain-boundary structure and segregation in Nb3Sn coatings on Nb for high-performance superconducting radiofrequency cavity applications. (15th April 2020) - Lee, Jaeyel; Mao, Zugang; He, Kai; Sung, Zu Hawn; Spina, Tiziana; Baik, Sung-Il; Hall, Daniel L.; Liepe, Matthias; Seidman, David N.; Posen, Sam
Abstract: We report on atomic-scale analyses of grain boundary (GB) structures and segregation in Nb3 Sn coatings on Nb, prepared by the vapor-diffusion process, for superconducting radiofrequency (SRF) cavity applications, utilizing atom-probe tomography, high-resolution scanning transmission electron-microscopy and first-principles calculations. We demonstrate that the chemical composition of Nb3 Sn GBs is correlated strongly with the diffusion of Sn and Nb at GBs during the coating process. In a sample coated with a relatively large Sn flux, we observe an interfacial width of Sn segregation at a GB of ∼3 nm, with a maximum concentration of ∼35 at.%. After post-annealing at 1100 °C for 3 h, the Sn segregated at GBs disappears and Nb segregation is observed subsequently at GBs, indicating that Nb diffused into the Nb3 Sn GBs from the Nb substrate. It is also demonstrated that the amount of Sn segregation in a Nb3 Sn coating can be controlled by: (i) Sn flux; and (ii) the temperatures of the Nb substrates and Sn source, which may affect the overall kinetics including GB diffusion of Sn and Nb. An investigation of the correlation between the chemical compositions of GBs and Nb3 Sn SRF cavity performance reveals that the Nb3 Sn SRF cavities with the best performance (high-quality factors at high accelerating electric-field gradients) do not exhibit Sn segregation at GBs. Our results suggest that the chemical compositions of GBs in Nb3 Sn coatings for SRF cavities can be controlled by GB engineering and can be utilized to optimize fabrication of high-quality Nb3 Sn coatings for SRF cavities. Graphical abstract: Image, graphical abstract